Advanced Routes in Synthesis and Reactions of Lawsone Molecules (2‐Hydroxynaphthalene‐1, 4‐dione). (3rd May 2017) - Hamama, Wafaa S.; Hassanien, Alaa El‐Din E.; Zoorob, Hanafi H.
Abstract : Lawsone (2‐hydroxynaphthalene‐1, 4‐dione ) is a natural product which shows significant biological activity. Lawsone has been found as a component of many dyes as well as a constituent of medicinal herbal treatments. So, this review aimed to document the publications concerning the synthesis and chemical reactivity and reactions of lawsone reported by research groups. Abstract :